2013
DOI: 10.1051/0004-6361/201321869
|View full text |Cite
|
Sign up to set email alerts
|

APEX/SABOCA observations of small-scale structure of infrared-dark clouds

Abstract: Infrared-dark clouds (IRDCs) harbor the early phases of cluster and high-mass star formation and are comprised of cold (∼20 K), dense (n > 10 4 cm −3 ) gas. The spectral energy distribution (SED) of IRDCs is dominated by the far-infrared and millimeter wavelength regime, and our initial Herschel study examined IRDCs at the peak of the SED with high angular resolution. Here we present a follow-up study using the SABOCA instrument on APEX which delivers 7.8 angular resolution at 350 µm, matching the resolution w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 77 publications
(148 reference statements)
3
33
1
Order By: Relevance
“…Due to the small sample size under discussion here, we merely use T bol as a proxy for relative evolutionary stage and do not speculate further whether the trends seen in the line emission hold universally. Strictly speaking, all cores fall below the fiducial T bol = 70 K threshold proposed by André et al (1993), qualifying all sources as Class 0 cores, but as was demonstrated in Ragan et al (2013) and Stutz et al (2013), T bol faithfully follows the evolution within this phase, such that more evolved cores have higher values of T bol .…”
Section: Core Evolution Signaturesmentioning
confidence: 64%
See 2 more Smart Citations
“…Due to the small sample size under discussion here, we merely use T bol as a proxy for relative evolutionary stage and do not speculate further whether the trends seen in the line emission hold universally. Strictly speaking, all cores fall below the fiducial T bol = 70 K threshold proposed by André et al (1993), qualifying all sources as Class 0 cores, but as was demonstrated in Ragan et al (2013) and Stutz et al (2013), T bol faithfully follows the evolution within this phase, such that more evolved cores have higher values of T bol .…”
Section: Core Evolution Signaturesmentioning
confidence: 64%
“…The SEDs of cores were revisited in Ragan et al (2013) with the addition of high-resolution (7. 8) SABOCA data at 350 µm.…”
Section: Continuum Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, high-mass clumps are not observed to be less dense than low-mass ones. If anything, they tend to be denser, and they are typically highly Jeans-unstable (Battersby et al, 2010;Ragan et al, 2012Ragan et al, , 2013Marsh et al, 2014).…”
Section: Stellar Imfmentioning
confidence: 99%
“…The study of low-mass (<10 M e ) starless cores has received considerable attention owingto their proximity and the systematic mapping of nearby molecular clouds in the GouldBelt (Ward- Thompson et al 1994;Tafalla et al 2004;André et al 2007André et al , 2013. In contrast, the study of intermediateand high-mass starless cores and clumps is still in a nascent state owing in part to their greater distances and few systematic observations to identify them (Tackenberg et al 2012;Wilcock et al 2012;Ragan et al 2013;Traficante et al 2015a). Our understanding of bothhow cluster formation is initiated and theensuing protocluster evolutionultimately depends on identifying and constraining the physical properties of representative samples of high-mass starless clumps.…”
Section: Introductionmentioning
confidence: 99%